MukB Is a Gene Necessary for Rapid Proliferation of Vibrio vulnificus in the Systemic Circulation but Not at the Local Infection Site in the Mouse Wound Infection Model - Takashige Kashimoto; Kohei Yamazaki; Takehiro Kado; Kaho Matsuda; Shunji Ueno (Microorganisms, 2021)
Vibrio vulnificus causes rapid septicemia in susceptible individuals who have ingested contaminated foods or have open wounds exposed to seawater contaminated with the bacteria. Despite antibiotic therapy and aggressive debridement, mortality from septicemia is high. In this study, we showed that MukB mutation (mukB::Tn) affected the proliferation of V. vulnificus in the systemic circulation but not at the inoculation site in the wound infection model. A comparison of mukB::Tn with WT and a mukB complement strain (mukB::Tn/pmukB) on the bacterial burden in the muscle at the infection site showed that spreading and proliferation of the mukB::Tn strain was similar to those of the other strains. However, the bacterial burden of mukB::Tn in the spleen was reduced compared to that of the WT strain in the wound infection model. In a competition experiment, we found a lower bacterial burden of mukB::Tn in the spleen than that of the WT strain infecting the systemic circulation. Here, we report on a gene required for the rapid proliferation of V. vulnificus only in the systemic circulation and potentially required for its survival. Our finding may provide a novel therapeutic target for V. vulnificus septicemia.